Correlation and path coefficient studies of Cocoyam (Xanthosoma sagittifolium L.) (Bangladesh Journal of Scientific and Industrial Research, 2015)
Plant height, leaf length, leaf breadth, leaf number, leaf area index, corm length, corm breadth, corm weight, sucker number exhibited positive correlation with yield per plant in both genotypic and phenotypic level in cocoyam (Xanthosoma sagittifolium). Path coefficient analysis revealed that leaf length, leaf number, corm length exhibited direct influences to yield per plant. In genotypic level yield per plant showed the highest positive direct effect with corm length followed by cormel breadth, sucker number.Bangladesh J. Sci. Ind. Res. 50(1), 47-52, 2015